PREVALENCE OF WASTING AND ASSOCIATED FACTORS AMONG CHILDREN AGED 6–59 MONTHS WITH PNEUMONIA AT HAI PHONG CHILDREN’S HOSPITAL, 2025–2026 (Vietnam Journal of Community Medicine, 2026)
Background: Wasting is common among children with pneumonia and may worsen disease progression.Objectives: To describe the prevalence of wasting and identify associated factors among children aged 6–59 months with pneumonia.Methods: A cross-sectional study was conducted among 590 children aged 6–59 months with pneumonia at Hai Phong Children’s Hospital from March 1, 2025 to February 28, 2026. Wasting was defined according to WHO criteria as a weight-for-height Z-score < −2 SD. Multivariable logistic regression was used to identify factors independently associated with wasting.Results: The prevalence of wasting was 10.3%. Factors independently associated with wasting included CRP ≥10 mg/L, anemia, history of COVID-19, early weaning, and maternal education level ≤ high school.Conclusions: Wasting remains common among children aged 6–59 months with pneumonia. Early nutritional assessment and intervention should be integrated into the management of children with pneumonia.
Keywords: Wasting; Pneumonia; Children aged 6–59 months; Malnutrition.